For the Love of Rain - Gable, Hannah (Cornfield Review, 2018)
For the Love of Rain allows you to understand and see the point of view from a very depressed individual. The love of his/her life has left them for good and they are unsure how to go on with life. They live in the shadow of their deep depression refusing to get help because they believe it will soon pass and their heart will receive the glowing warmth that they once had. However, they are not only depressed. They are hurt, angered, and living with mingling fear of seeing their beloved with someone else and becoming more shattered.